# How do you evaluate [4-(7-5(2-3)+2]+3?

Jun 23, 2015

ops...there is one bracket missing!!! I'll try two configurations:

#### Explanation:

1] After $2$: $\left[4 - \left(7 - 5 \left(2 - 3\right) + 2 \textcolor{red}{\to}\right)\right] + 3 =$

$\left[4 - \left(7 - 5 \left(2 - 3\right) + 2\right)\right] + 3 =$
I would try with this:
Bracket:
$= \left[4 - \left(7 - 5 \textcolor{red}{\left(2 - 3\right)} + 2\right)\right] + 3 =$
$= \left[4 - \left(7 - 5 \textcolor{red}{\left(- 1\right)} + 2\right)\right] + 3 =$
Now multiplication (inside the bracket):
$= \left[4 - \left(7 - \textcolor{b l u e}{5 \left(- 1\right)} + 2\right)\right] + 3 =$
$= \left[4 - \left(7 + 5 + 2\right)\right] + 3 =$
and solve inside the bracket:
$= \left[4 - 14\right] + 3 = - 10 + 3 = - 7$

2] After $3$: $\left[4 - \left(7 - 5 \left(2 - 3\right) \textcolor{red}{\to}\right) + 2\right] + 3 =$

$\left[4 - \left(7 - 5 \left(2 - 3\right)\right) + 2\right] + 3 =$
almost as before BUT...!!!
$= \left[4 - \left(7 - 5 \left(- 1\right)\right) + 2\right] + 3 =$
$= \left[4 - \left(7 + 5\right) + 2\right] + 3 =$
$= \left[4 - 12 + 2\right] + 3 =$
$= - 6 + 3 = - 3$ !!!!!